Penilaian Kesehatan Bank (Studi Pada PT. Bank Muamalat Indonesia, Tbk. Tahun 2016- 2019) - Permata, Citra Puspa (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the financial health of PT. Bank Muamalat Indonesia, Tbk from four aspects in RGEC which is Risk Profile, Good Corporate Governance, Earnings, and Capital. This research is a descriptive study with a quantitative approach. The main data of this study comes from the Annual Report of PT. Bank Muamalat Indonesia, Tbk. from 2016 to 2019, the so-called secondary data were analyzed using the RGEC method. The results showed that in the period 2016-2019, the risk profile aspect of PT. Bank Muamalat Indonesia with the NPF and FDR Indicator on average is in a healthy financial condition, but the CR indicator showed unhealthy financial conditions. The GCG aspect using self-assessment showed a fairly healthy financial condition, the earnings aspect. with NOM, ROA and average ROE showed unhealthy financial conditions, as well as the capital aspect with average CAR and PR ratios is in very healthy financial conditions.